2000
DOI: 10.1001/archsurg.135.3.326
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Resuscitation Fluid Volumes in Severely Burned Patients Using Ascorbic Acid Administration

Abstract: High-dose ascorbic acid (vitamin C) therapy (66 mg/kg per hour) attenuates postburn lipid peroxidation, resuscitation fluid volume requirements, and edema generation in severely burned patients. Study Design and Setting:A prospective, randomized study at a university trauma and critical care center in Japan.Subjects and Methods: Thirty-seven patients with burns over more than 30% of their total body surface area (TBSA) hospitalized within 2 hours after injury were randomly divided into ascorbic acid and contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
318
1
16

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 399 publications
(341 citation statements)
references
References 32 publications
(38 reference statements)
1
318
1
16
Order By: Relevance
“…This concentration is equal to the plasma ascorbate concentration achieved by an ascorbate infusion protocol that lessens edema formation in burn patients (57). For the ascorbate and DHAA treatments in cell cultures, the protection of the endothelial barrier is associated with increased intracellular ascorbate concentration and it depends on inhibition of both peroxynitrite formation and PP2A nitration/ activation (24).…”
Section: Vitamin C Therapy For Sepsismentioning
confidence: 99%
See 2 more Smart Citations
“…This concentration is equal to the plasma ascorbate concentration achieved by an ascorbate infusion protocol that lessens edema formation in burn patients (57). For the ascorbate and DHAA treatments in cell cultures, the protection of the endothelial barrier is associated with increased intracellular ascorbate concentration and it depends on inhibition of both peroxynitrite formation and PP2A nitration/ activation (24).…”
Section: Vitamin C Therapy For Sepsismentioning
confidence: 99%
“…The first of these 2 trials found that infusion i.v. of ascorbate [1584 mg/(kg.day)] decreases edema and improves respiratory function in severely burned patients (57). This trial is relevant because, first, there are similarities between the systemic inflammatory responses to septic insults and burn injury, and second, a major cause of death in severely burned patients is multiorgan failure due to sepsis.…”
Section: Mortality and Morbiditymentioning
confidence: 99%
See 1 more Smart Citation
“…The length of mechanical ventilation was also significantly reduced and improved early respiratory function was observed. 112 Other micronutrients that have received attention in recent years include vitamin D and vitamin B 12 . Vitamin D deficiency states have been described in patients with severe sepsis and other critically ill populations 113,114 with low levels of vitamin D-binding hormone being reported.…”
Section: Cccpg Aspen/sccm Espenmentioning
confidence: 99%
“…The clinical studies, performed in Japan, suggest that Vitamin C treatment might be an inexpensive and effective means for reducing fluid requirements for burn patients 84 . These studies have not been duplicated in other institutions.…”
Section: Pharmacologic Manipulation Of Resuscitationmentioning
confidence: 99%